2021
DOI: 10.9734/jammr/2021/v33i1631013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anaemia at Booking amongst Antenatal Clinic Attendees in Some Health Facilities in Ogoni, South-South Nigeria

Abstract: Background: Anaemia in pregnancy is an indirect cause of maternal mortality. Myriad of factors predispose pregnant women to anaemia in pregnancy in the developing countries of the world of which poverty, illiteracy and ignorance are central. The prevalence of anaemia in the developing countries of the world is between 32% and 62.2%. Objective: To determine the prevalence of anaemia amongst antenatal clinic attendees in Ogoni, South-South Nigeria and offer preventive measures. Material and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…This was not in agreement with the study conducted by Eli S et al in the rural community of Ogoni in Nigeria where 72.3% of the antenatal clinic attendees had secondary level of education whereas 18% had tertiary level of education. [21]…”
Section: Discussionmentioning
confidence: 99%
“…This was not in agreement with the study conducted by Eli S et al in the rural community of Ogoni in Nigeria where 72.3% of the antenatal clinic attendees had secondary level of education whereas 18% had tertiary level of education. [21]…”
Section: Discussionmentioning
confidence: 99%
“…5-6 83.1% in South East Nigeria. [5][6][7] Studies have shown that majority of women who registered for antenatal clinic present when they have symptoms of diseases like following illness in pregnancy, presenting with fever, joint pains. [7] Seventy percent of these women were on treatment for malaria by a doctor and 30% were on treatment for malaria by a nurse.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] The average gestational age at booking in Riyadh Sandi Arabia was 13 weeksthe mean gestational age at booking in different cities in Nigeria was 19.1 ±7.8 weeks in Lagos, 21.8 ±7.0 weeks in Ibadan, and 23.5 ±6 weeks in Sokoto. [2][3][4][5][6][7] From the study conducted in Lagos there were differences in the gestational age at booking in relation to parity. [2][3][4][5][6] While nulliparous women booked at a mean gestational age of 18.5 ±8.3 weeks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations